Tissue proteomics: methods and protocols - Sarwal, Minnie (Methods in molecular biology, 2018)
Depletion of Myofibril-Associated Proteins Using Selective Protein Extraction as a Tool in Cardiac Proteomics -- Discovery of Immune Reactive Human Proteins by High Density Protein Arrays and Customized Validation of Potential Biomarkers by ELISA -- HLA Class I and Class II-Induced Intracellular Signaling and Molecular Associations in Primary Human Endothelial Cells -- Characterization of Protein Complexes Using Chemical Cross-linking Coupled Electrospray Mass Spectrometry -- Optimization for Peptide Sample Preparation for Urine Peptidomics -- Purification of Target Proteins from Native Tissues: CCT Complex from Bovine Testes and PP2Ac from Porcine Brains -- Integrative Analysis of Proteomics Data to Obtain Clinically Relevant Markers -- Untargeted Screening of Urinary Peptides Using Off-line Nano-liquid Chromatography - MALDI-TOF/TOF Mass Spectrometry -- Identifying Clinically Relevant Proteins for Targeted Analysis in the Development of a Multiplexed Proteomic Biomarker Assay -- In Situ Hybridization and Double Immunohistochemistry for the Detection of VEGF-A mRNA and CD34/Collagen IV Proteins in Renal Transplant Biopsies -- LC-SRM-based Targeted Quantification of Urinary Protein Biomarkers -- Fractionation of Soluble Proteins Using DEAE-, SP-, and Phenyl Sepharose Chromatographies for Proteomics -- GeLC-MS: A Sample Preparation Method for Proteomics Analysis of Minimal Amount of Tissue -- Targeted Proteomics Verification of Breast Cancer Biomarker Candidates -- Combination Strategy of Quantitative Proteomics Uncovers the Related-Proteins of Colorectal Cancer in the Interstitial Fluid of Colonic Tissue from the AOM-DSS Mouse Model -- Multiple Reaction Monitoring using Double Isotopologue Peptide Standards for Protein Quantification -- Isobaric Labeling Based LC-MS/MS Strategy for Comprehensive Profiling of Human Pancreatic Tissue Proteome -- MALDI Imaging Mass Spectrometry of N-glycans and Tryptic Peptides from the same Formalin-Fixed, Paraffin-embedded Tissue Section -- Differential Adipose Tissue Proteomics -- Quantification of Breast Cancer Protein Biomarkers at Different Expression Levels in Human Tumors -- Quantitative Proteomic Analysis of Mass Limited Tissue Samples for Spatially-resolved Tissue Profiling -- High-throughput Proteomics Analysis of Fresh-frozen Biopsy Tissue Samples using Pressure Cycling Technology Coupled with SWATH Mass Spectrometry -- Straightforward Protocol for Gel-free Proteomic Analysis of Adipose Tissue -- MALDI Imaging Combined to Laser Microdissection-based Microproteomics for Protein Identification. Application to Intratumor Heterogeneity Studies.
Keywords: Aufsatzsammlung; Proteomanalyse; Gewebe